2021
DOI: 10.3389/fphar.2021.709019
|View full text |Cite|
|
Sign up to set email alerts
|

Ginsenoside Rg1 Ameliorates Neuroinflammation via Suppression of Connexin43 Ubiquitination to Attenuate Depression

Abstract: Depression is an inflammation-associated disease that results in major depression as inflammation increases and progresses. Ginsenoside Rg1 (Rg1), the major bioactive ingredient derived from ginseng, possesses remarkable anti-depressant and anti-inflammatory effects. Our previous studies showed that the pathogenesis of depression was concomitant with the acceleration of connexin43 (Cx43) ubiquitin degradation, while Rg1 could upregulate Cx43 expression to attenuate depression. However, whether the ubiquitinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Research has confirmed that Rg1 can inhibit neuroinflammation in neurological diseases [ 63 , 65 ]. However, most studies focus on the mechanism of pro-inflammatory factors [ 63 , 65 , 66 ], and few studies examine anti-inflammatory factors [ 58 ]. In future research, we can further study the effect of Rg1 on anti-inflammatory factors in neurological diseases, and how Rg1 affects the balance between anti-inflammatory and proinflammatory factors to improve neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has confirmed that Rg1 can inhibit neuroinflammation in neurological diseases [ 63 , 65 ]. However, most studies focus on the mechanism of pro-inflammatory factors [ 63 , 65 , 66 ], and few studies examine anti-inflammatory factors [ 58 ]. In future research, we can further study the effect of Rg1 on anti-inflammatory factors in neurological diseases, and how Rg1 affects the balance between anti-inflammatory and proinflammatory factors to improve neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Rg1 reduced the level of intracellular adhesion molecule 1 (ICAM-1), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS), as well as maintained the integrity of BBB permeability in neuroinflammation-induced behavioral deficits [ 65 ]. Studies have shown that Rg1 reduced the levels of IL-1β, TNF-α, caspase-1, IL-2, IL-6 and IL-18 via the suppression of Connexin43 (Cx43) ubiquitination in depression [ 66 ] ( Figure 3 ). Overall, there are few disease model studies on Rg1 inhibiting the neuroinflammatory response, and it is more about inhibiting the expression of inflammatory factors.…”
Section: Mechanismsmentioning
confidence: 99%
“…Likewise, Ginsenoside Rg1 is one of the constituents extracted from ginseng, with antidepressant and anti-inflammatory neuroprotective properties [ 159 ]. Ginsenoside Rg1 attenuates neuroinflammation by inhibiting Cx43 ubiquitination, thereby reducing depression [ 160 ]. Similarly, minocycline, an antibiotic, reduces the proinflammatory cytokines from activated microglia and relieves depression [ 161 ].…”
Section: Cx43 As a Mediator Of Neuroinflammation And Depressionmentioning
confidence: 99%
“…Ginsenoside Rg1, one of the most prominent active components in ginseng that is a distinguished herbal medicine, possesses antioxidant, antiaging, and immune and memory improving properties. [25][26][27][28] Compelling reports have unveiled the therapeutic effects of ginsenoside Rg1 on kidney-related diseases: for instance, ginsenoside Rg1 can protect human renal TECs from LPS-elicited apoptosis and inflammatory injury 29 ; ginsenoside Rg1 imposes protection on antiglomerular basement membrane glomerular nephritis through activation of the NRF2 pathway 30 ; ginsenoside Rg1 represses angiotensin II-triggered podocyte autophagy through the AMPK/mTOR/PI3K pathway. 31 Previous research has documented that ginsenoside Rg1 could protect against kidney injury by attenuating oxidative stress.…”
Section: Introductionmentioning
confidence: 99%